Advances in Transcriptomics in the Response to Stress in Plants - Wang, Xiaojuan; Li, Na; Li, Wei; Gao, Xinlei; Cha, Muha; Qin, Lijin; Liu, Lihong (Global Medical Genetics, 2020)
Adverse stress influences the normal growth and development of plants. With the development of molecular biology technology, understanding the molecular mechanism of plants in response to adverse stress has gradually become an important topic for academic exploration. The expression of the transcriptome is dynamic, which reflects the level of expression of all genes in a particular cell, tissue, or organ of an individual organism at a particular stage of growth and development. Transcriptomics can disclose the expression at the whole genome level under stress from the whole transcriptional level, which can be useful in understanding the complex regulatory network associated with the adaptability and tolerance of plants to stress. In this article, we review the application of transcriptomics in understanding the response of plants to biotic stresses such as diseases and insect infestation and abiotic stresses such as water, temperature, salt, and heavy metals to provide a guideline for related research.
Keywords: transcriptomics; biotic stress; abiotic stresses